Neutron energy spectrum flux profile of Ghana's miniature neutron source reactor core - Sogbadji, R.B.M.; Abrefah, R.G.; Ampomah-Amoako, E.; Agbemava, S.E.; Nyarko, B.J.B. (Annals of Nuclear Energy, 2011)
The total neutron flux spectrum of the compact core of Ghana's miniature neutron source reactor was understudied using the Monte Carlo method. To create small energy groups, 20,484 energy grids were used for the three neutron energy regions: thermal, slowing down and fast. The moderator, the inner irradiation channels, the annulus beryllium reflector and the outer irradiation channels were the region monitored. The thermal neutrons recorded their highest flux in the inner irradiation channel with a peak flux of (1.2068 ± 0.0008) × 1012 n/cm2 s, followed by the outer irradiation channel with a peak flux of (7.9166 ± 0.0055) × 1011 n/cm2 s. The beryllium reflector recorded the lowest flux in the thermal region with a peak flux of (2.3288 ± 0.0004) × 10 11 n/cm2 s. The peak values of the thermal energy range occurred in the energy range (1.8939-3.7880) × 10-08 MeV. The inner channel again recorded the highest flux of (1.8745 ± 0.0306) × 1009 n/cm2 s at the lower energy end of the slowing down region between 8.2491 × 10-01 MeV and 8.2680 × 10-01 MeV, but was over taken by the moderator as the neutron energies increased to 2.0465 MeV. The outer irradiation channel recorded the lowest flux in this region. In the fast region, the core, where the moderator is found, the highest flux was recorded as expected, at a peak flux of (2.9110 ± 0.0198) × 1008 n/cm2 s at 6.961 MeV. The inner channel recorded the second highest while the outer channel and annulus beryllium recorded very low flux in this region. The flux values in this region reduce asymptotically to 20 MeV. © 2011 Elsevier Ltd. All rights reserved.
Keywords: Energy; Flux; Moderation; Monte Carlo; Neutron; Spectrum